CD4 Percentage and Absolute CD4 Accuracy not Different in Predicting Viral Load of HIVInfected Mothers - Santoso, Ferry; Suwiyoga, Ketut; Putra, I Gede M (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the accuracy difference between CD4 percentage and absolute CD4 in predicting the viral load of HIV-infected pregnant women. Methods: This study is a diagnostic study involving 22 HIV-infected pregnant women who came for PMTCT at the Outpatient Clinic in Sanglah Hospital, from September 2011 until August 2012, who were randomly selected through consecutive sampling. Blood samples were collected to analyze the viral load, CD4, and complete blood count (CBC). Viral load examination was conducted using PCR in the molecular biology laboratory in the Faculty of Medicine University of Udayana. CD4 and CBC test was conducted in Sanglah Hospital Laboratory. Analysis was done with 2x2 table using SPSS for windows® version 17 to evaluate sensitivity, specificity and accuracy rate of CD4 percentage and absolute CD4 in predicting the viral load. Results: Data analysis shows that CD4 percentage had 75.0% sensitivity, 88.9% specificity, and accuracy of 86.4% for predicting the viral load in HIV-infected pregnant women. Meanwhile, absolute CD4 had 50.0% sensitivity, 77.8% specificity, and 72.7% accuracy. Chisquare test shows that there was no significant difference in the accuracy of CD4 percentage and absolute CD4 (p=0.457). Conclusion: CD4 percentage and absolute CD4 had high accuracy in predicting the viral load in HIV-infected pregnant women (86.4% and 72.7%). There was no significant difference of accuracy between the CD4 percentage and absolute CD4. [Indones J Obstet Gynecol 2015; 3-4: 230-233] Keywords: CD4, HIV-infected pregnant women, viral load